Threshold Externalities in Economic Development - Azariadis, Costas; Drazen, Allan (Quarterly Journal of Economics, 1990)
Standard one-sector growth models often have the counterfactual implication that economies with access to similar technologies will converge to a common balanced growth path. We propose an elaboration of the Diamond model that permits multiple, locally stable stationary states. This multiplicity is due to increasing social returns to scale in the accumulation of human capital.